2017
DOI: 10.1186/s12943-017-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin mediates tumor-promoting effects of Interleukin-1beta in breast cancer cells

Abstract: BackgroundIt is widely recognized that inflammation promotes breast cancer invasion and metastasis. Given the complex nature of the breast tumor inflammatory microenvironment, much remains to be understood of the molecular mechanisms that govern these effects. We have previously shown that osteoprotegerin knockdown in breast cancer cells resulted in reduced invasion and metastasis. Here we present novel insight into the role of osteoprotegerin in inflammation-driven tumor progression in breast cancer by invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 57 publications
(76 reference statements)
2
18
0
Order By: Relevance
“…In breast cancer, higher concentrations of OPG were associated with an increased risk of ER-negative breast cancer (35). In addition, preclinical studies indicate that OPG mediates tumor-promoting effects as a mediator of inflammation in breast cancer (36) and promotes metastases in triple-negative breast cancer (37). Our data are in line with these results, implying that high levels of OPG, although potentially bone protective, actually confer a poor prognosis in certain malignancies including breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, higher concentrations of OPG were associated with an increased risk of ER-negative breast cancer (35). In addition, preclinical studies indicate that OPG mediates tumor-promoting effects as a mediator of inflammation in breast cancer (36) and promotes metastases in triple-negative breast cancer (37). Our data are in line with these results, implying that high levels of OPG, although potentially bone protective, actually confer a poor prognosis in certain malignancies including breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1β (IL-1β), a pro-inflammatory cytokine is implicated in cancer cell proliferation [1], emerging now as a key mediator of carcinogenesis. Its involvement in the molecular pathways of cancer-related inflammation are being unravelled, especially in pancreatic [2], breast [3] and prostate cancers [4]. Monitoring this biomarker in point-of care may therefore contribute to follow-up the progress of cancer diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that there is an increase in OPG gene copy number in breast cancers and that this increase correlates with poor survival (38). In addition, we have shown that OPG expression is up-regulated in breast cancer cells cocultured with macrophages and this is in part due to the presence of Interleukin 1Beta (39). These studies demonstrate the potential for increased OPG expression in breast cancer, but the mechanisms for down-regulation with increasing tumor grade require further investigation.…”
Section: Discussionmentioning
confidence: 66%